Goin' crazy with Sam Peckinpah and all our friends - Evans, Max (Univ. of New Mexico Press, 2014)
"Almost as famous for the legendary excesses of his personal life as for his films, Sam Peckinpah (1925-1984) cemented his reputation as one of the great American directors with movies such as The Wild Bunch and Pat Garrett and Billy the Kid. Max Evans, one of Peckinpah's best friends, experienced the director's mercurial character and personal demons firsthand. In this enthralling memoir we follow Evans and Peckinpah through conversations in bars, family gatherings, binges on drugs and alcohol, struggles with film producers and executives, and Peckinpah's abusive behavior--sometimes directed at Evans himself. Evans's stories--most previously unpublished--provide a uniquely intimate look at Peckinpah, their famous friends (including Lee Marvin, Brian Keith, Joel McCrea, and James Coburn), and the business of Hollywood in the 1960s and 1970s"--